DELEGATION OF AUTHORITY FOR MEDICAL ACTION FROM DOCTORS TO NURSES IN HEALTH SERVICES FACILITIES: PELIMPAHAN WEWENANG TINDAKAN MEDIS DARI DOKTER KEPADA PERAWAT DI FASILITAS PELAYANAN KESEHATAN - Irvan Eka Gumelar; Dey Ravena (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
This delegation of authority for medical action from doctors to nurses is prioritized by looking at the qualification, abilities, competencies and experience in the field of health sciences. The description of nurse‟s authority in carrying out the duties is mandated in law Number 38 0f 2014 concering nursing. the most common is the difference is meaning between medical ethics and nursing ethics. Both terms are based on two English verbs “to cure” and “to care”. The main task of the doctor is to cure, which includes the diagnosis of disease. While the nurses completes the activities of doctors by treating according to his scientific discipline. This paper aims to find out and understand the importance of delegating the authority of medical action from doctors to nurses in health care.